2017
DOI: 10.1111/dar.12554
|View full text |Cite
|
Sign up to set email alerts
|

Support for alcohol policies from drinkers in the City of Tshwane, South Africa: Data from the International Alcohol Control study

Abstract: Introduction and Aims. South Africa is considering a range of alcohol policy reforms. This study aims to determine the magnitude of public support for 13 alcohol policies in the Tshwane Metropolitan Municipality and whether this varies by demographic factors and heavy drinking status. Design and Methods. Data are from the South African arm of the International Alcohol Control study, a household survey of adult drinkers using a multistage stratified cluster random sampling design. The sample included 1920 drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Policy support in South Africa, a high–middle‐income country, was not always greater than in New Zealand. This could be because other research has shown that there are very high levels of heavy drinking in South Africa and it is well recognised that heavier drinkers are less likely to support more restrictive alcohol policies .…”
Section: Discussionmentioning
confidence: 99%
“…Policy support in South Africa, a high–middle‐income country, was not always greater than in New Zealand. This could be because other research has shown that there are very high levels of heavy drinking in South Africa and it is well recognised that heavier drinkers are less likely to support more restrictive alcohol policies .…”
Section: Discussionmentioning
confidence: 99%
“…There were four stages to the cluster random sampling involving sampling of wards (Stage 1), enumeration areas (EAs) within selected wards (Stage 2), households within selected EAs (Stage 3), and study participants within selected households (Stage 4). This is described in detail elsewhere [ 25 ]. Data were weighted to take into account the underlying structure of the realized sample and the sample frame to ensure a random selection of respondents.…”
Section: Methodsmentioning
confidence: 99%
“…The target sample size of 2000 was determined by the IAC Study [ 23 ]. The overall response rate was 78% [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies have concluded that alcohol reforms and policies are likely to be resisted by individuals who are directly impacted by alcohol control measures (Parry, Trangestein, Lombard, Jernigan, & Morojele, 2017;Tobin, Moodie, & Livingstone, 2011). In the context of the Nordic countries, Sulkunen and Warsell (2012) have argued that tax increases and reducing availability of alcohol are likely to be unpopular because they "interfere with the freedom of consumers to choose" (p. 218).…”
Section: Discussionmentioning
confidence: 99%